2010
DOI: 10.1021/ef9013407
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocracking of Athabasca Bitumen Using Submicronic Multimetallic Catalysts at Near In-Reservoir Conditions

Abstract: NiWMo submicronic catalysts from emulsified metallic aqueous solutions were tested for Athabasca bitumen upgrading. The experiments were performed in a batch reactor (100 mL capacity) at a total pressure of 3.45 MPa, a stirring speed of 500 rpm, reaction times of 3−70 h, and temperatures from 320 to 380 °C. Ultradispersed (UD) catalysts enhanced the upgrading of Athabasca bitumen by increasing the hydrogen/carbon ratio and reducing both viscosity and coke formation. The conversion of bitumen increased with bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
99
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(110 citation statements)
references
References 24 publications
9
99
0
2
Order By: Relevance
“…However, most of these techniques do not exceed 20 %-25 % oil recovery or 50 % for the steam-assisted gravity drainage (SAGD) process (Butler 1998;Nasr et al 2003;Hashemi et al 2013). Nanoparticle technology has emerged as an alternative with a great potential to improve the previously mentioned techniques and increase oil recovery (Hashemi et al 2014a, b, c;Galarraga and Pereira-Almao 2010;Hashemi et al 2012;Franco et al 2013aFranco et al , b, 2014Hosseinpour et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…However, most of these techniques do not exceed 20 %-25 % oil recovery or 50 % for the steam-assisted gravity drainage (SAGD) process (Butler 1998;Nasr et al 2003;Hashemi et al 2013). Nanoparticle technology has emerged as an alternative with a great potential to improve the previously mentioned techniques and increase oil recovery (Hashemi et al 2014a, b, c;Galarraga and Pereira-Almao 2010;Hashemi et al 2012;Franco et al 2013aFranco et al , b, 2014Hosseinpour et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…The challenges of packing the horizontal production well with pelleted catalyst and deactivation caused by coke and metal deposition could potentially be decreased by using ultradispersed, once-through nano-sized catalyst. Galarraga and Pereira-Almao [9] reported the use of a trimetallic (Ni-W-Mo) submicronic catalyst for dispersed upgrading at 380°C in a batch reactor, using a stirrer speed of 500 rpm, and a reaction time of 3-70 h. They found that the produced oil API gravity increased by 6.5°API and the extent of viscosity reduction was 99% relative to the Athabasca bitumen (API gravity 9.5 and viscosity 7680 mPa·s).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover nano-sized catalysts have a high surface to volume ratio, low intraparticle mass transfer resistance and thus may be more resistant to deactivation than pelleted catalysts [9,11]. Ultrafine (micron) scale particles may also offer some of these advantages whilst being cheaper to produce, not requiring specialist preparation and easier to handle, for example not being absorbed easily through the skin.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, many homogeneously dispersed catalysts have been studied and developed, which could be formulated as water-soluble catalysts [13][14][15][16] and oil-soluble catalysts [17][18][19][20][21]. Homogeneously dispersed catalysts are metal compounds, and the metal is selected from elements of group IV B-VIII among which the molybdenum, nickel, cobalt and chromium are commonly used [22][23][24][25]. The homogeneously dispersed catalyst and feedstock oil were added into the reactor simultaneously, the catalyst was actually a precursor which could be converted to the active metal sulfides through a sulfuration reaction.…”
Section: Introductionmentioning
confidence: 99%